2019
DOI: 10.3389/fonc.2019.00562
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complexes Containing Heterocyclic Thioamidates Trigger Caspase-Mediated Apoptosis Through MAPK Signaling in Human Hepatocellular Carcinoma Cells

Abstract: Herein, ruthenium complexes containing heterocyclic thioamidates [Ru(mmi)(bipy)(dppb)]PF 6 ( 1 ), [Ru(tzdt)(bipy)(dppb)]PF 6 ( 2 ), [Ru(dmp)(bipy)(dppb)]PF 6 ( 3 ) and [Ru(mpca)(bipy)(dppb)]PF 6 ( 4 ) were investigated for their cellular and molecular effects in cancer cell lines. Complexes 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…In recent studies, ruthenium(II) complex with methylimidazole induced cell cycle arrest at G 0 /G 1 phase and caused apoptosis through ROS, MAPK and AKT signaling pathways in human lung carcinoma A549 cells 32 , meanwhile ruthenium(II) complex with xanthoxylin caused S-phase arrest and ERK1/2-mediated apoptosis in HepG2 cells by a p53-independent pathway 10 . Similar results were found by Neves and collaborators 16 with ruthenium complexes containing heterocyclic thioamidates that caused caspase-mediated apoptosis through MAPK signaling in HepG2 cells. Ruthenium(II) complexes with piplartine induced MAPK- and p53-dependent apoptosis in HCT116 cells by a ROS-mediated pathway 7,15 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In recent studies, ruthenium(II) complex with methylimidazole induced cell cycle arrest at G 0 /G 1 phase and caused apoptosis through ROS, MAPK and AKT signaling pathways in human lung carcinoma A549 cells 32 , meanwhile ruthenium(II) complex with xanthoxylin caused S-phase arrest and ERK1/2-mediated apoptosis in HepG2 cells by a p53-independent pathway 10 . Similar results were found by Neves and collaborators 16 with ruthenium complexes containing heterocyclic thioamidates that caused caspase-mediated apoptosis through MAPK signaling in HepG2 cells. Ruthenium(II) complexes with piplartine induced MAPK- and p53-dependent apoptosis in HCT116 cells by a ROS-mediated pathway 7,15 .…”
Section: Discussionsupporting
confidence: 88%
“…Ruthenium-based metallodrugs have been emerged as a novel potential antineoplastic class with less side effect than platinum-based complexes. Therefore, many ruthenium complexes have been synthesized and assessed for their antineoplastic potential in both preclinical and clinical stages, with encouraging outcomes 516 .…”
Section: Introductionmentioning
confidence: 99%
“…ERK is a protein-serine/threonine kinase that can activate nuclear transcription factors and is involved in cell proliferation, differentiation and cell death [39][40][41][42]. It has been confirmed that the proliferative role of ghrelin is related to the activation of its downstream MAPK signaling cascade in multiple types of cells [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Human Hepatocellular Carcinoma Xenograft Model . Human hepatocellular carcinoma xenograft model was carried out as previously reported [30–32] . Fifty C.B‐17 SCID mice (females, 25–30 g) obtained at the animal facilities of the Gonçalo Moniz Institute‐FIOCRUZ (Salvador, Bahia, Brazil) were used.…”
Section: Methodsmentioning
confidence: 99%